Enhancing knowledge discovery and innovation in the digital era - Lytras, Miltiadēs 1973-; Daniela, Linda; Visvizi, Anna 1976- (Advances in knowledge acquisition, transfer, and management (AKATM) book series, 2018)
"This book analyzes various aspects of the knowledge society. It anchors government policies and examines the characteristics of the emerging knowledge intensive economy and social environment. It investigates key priorities of the knowledge society in terms of critical aspects of human life (e.g. health, education, culture, science, business, etc.)"--